Disruption of RB/E2F-1 interaction by single point mutations in E2F-1 enhances S-phase entry and apoptosis. - Shan, B (1996)
The retinoblastoma protein (RB) has been proposed to function as a negative regulator of cell proliferation by complexing with cellular proteins such as the transcription factor E2F. To study the biological consequences of the RB/E2F-1 interaction, point mutants of E2F-1 which fail to bind to RB were isolated by using the yeast two-hybrid system. Sequence analysis revealed that within the minimal 18-amino acid peptide of E2F-1 required for RB binding, five residues, Tyr (position 411), Glu (419), and Asp-Leu-Phe (423-425), are critical. These amino acids are conserved among the known E2F family members. While mutation of any of these five amino acids abolished binding to RB, all mutants retained their full transactivation potential. Expression of mutated E2F-1, when compared with that of wild-type, significantly accelerated entry into S phase and subsequent apoptosis. These results provide direct genetic evidence for the biological significance of the RB/E2F interaction and strongly suggest that the interplay between RB and E2F is critical for proper cell cycle progression.